2016
DOI: 10.1371/journal.pone.0162526
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolutionary Pathways toward Two Successful Community-Associated but Multidrug-Resistant ST59 Methicillin-Resistant Staphylococcus aureus Lineages in Taiwan: Dynamic Modes of Mobile Genetic Element Salvages

Abstract: Clonal complex 59 (CC59) Staphylococcus aureus in Taiwan includes both methicillin-susceptible S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA). As the most prominent community-associated MRSA (CA-MRSA) in Taiwan, CC59 has two major clones characterized as PVL-negative SCCmec IV (carrying the staphylococcal cassette chromosome mec IV but Panton-Valentine leukocidin-negative) and PVL-positive SCCmec V (5C2&5). We investigated the drug resistance, phylogeny and the distribution and sequence variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Previous studies have demonstrated that ST59 is becoming the predominant MRSA sequence type isolated from hospitalized patients in China (Chuang and Huang, 2013;Yang et al, 2017;Li et al, 2018). There are two distinct clones within the ST59 sequence type, AP, which is PVL-negative/SAK-positive, and TW, which is PVLpositive/SAK-negative (Hung et al, 2016). Both of these clones were identified in our analysis (Figure 1); however, both clones underwent significant genetic changes.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have demonstrated that ST59 is becoming the predominant MRSA sequence type isolated from hospitalized patients in China (Chuang and Huang, 2013;Yang et al, 2017;Li et al, 2018). There are two distinct clones within the ST59 sequence type, AP, which is PVL-negative/SAK-positive, and TW, which is PVLpositive/SAK-negative (Hung et al, 2016). Both of these clones were identified in our analysis (Figure 1); however, both clones underwent significant genetic changes.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have suggested that ST59 evolved concurrently in both North America (NA), previously referred to as the United States lineage and East Asia (EA), with strains from each region belonging to separate and distinct sub-lineages ( Ward et al, 2016 ), with mobile genetic elements playing a part ( Hung et al, 2016 ). For a more detailed look into the evolution of the ST59 lineage, a Bayesian inference phylogenomic tree, comprised of both the monomorphic SNPs and insertions/deletions identified by snippy, was generated incorporating our isolates (red font), as well as select isolates from the Ward et al (2016) (blue font) and Pang et al (2020) (green font) studies, and ST59 sequences downloaded from NCBI (black font).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have attempted to explain evolution of the lineage, not only identifying separate sub-lineages, but also identifying factors that contributed to expansion and success of the each of the sub-lineage. Studies by Hung et al (2016) and Pang et al (2020) focused on ST59 success on a local scale, investigating the lineage in Taiwan and mainland China, respectively, while a study by Ward et al (2016) examined evolution of the lineage on the global scale. All studies noted that acquisition of mobile genetic elements such as IEC, MES, SCC mec , and PVL contributed to diversification of the lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by the genotype ST1/SCC mec IVa, Panton-Valentine leukocidin (PVL) genes and lower multidrug resistance than HA-MRSA. Global examples of CA-MRSA include the genotypes ST8/SCC mec IV (particularly USA300, which has caused serious outbreaks [1] , [2] , [4] , [5] , [6] ), ST30/SCC mec IV, ST59/SCC mec V [7] and ST80/SCC mec IV (particularly in Europe [8] ). Although SCC mec IV (like SCC mec V) is common among CA-MRSA strains [2] , its role in the pathogenesis of MRSA remains unclear.…”
Section: Introductionmentioning
confidence: 99%